Effects of coastal development on ship manoeuvring and navigation - Mohd. Noor, Hamzah; Maimun, Adi; Abd. Wahab, Ahmad Khairi; Ismail, Hadibah; Priyanto, Agoes; Muhammad, A. Haris (2006)
Coastal development, such as land reclamation or dredging, usually changes the characteristics of the coastal waterway. A common phenomena due to restricted waterway is increase in ship resistance and reduction in manoeuvrability. The restricted water inflow under the vessel, result in increased water velocity under the hull. The increase of the inflow velocity at the rudder may result in the increase of the rudder normal force or create partial vacuum in the region near propeller and rudder. Consequently, manoeuvring of ships may become erratic in this condition. Standard for ship maneuvrabiity have been developed by International Maritime Organization (IMO) to ensure safe navigation/ship handling operation of ships. The standards provide criteria on the ship turning ability, yaw checking ability, course keeping ability and stopping ability. Where there is uncertainty in the behavior of the vessel especially in restricted waters, the use of numerical simulation for evaluating navigational risks is highly depended upon. In this paper, firstly, the effects on water depths and currents due to coastal development will be described. Secondly, using time domain simulation approach, the manoeuvring characteristics of vessel in two scenarios, i.e. deep and shallow water are discussed. Thirdly, actual simulations demonstrating the risks involved in navigating in a restricted waterway will be demonstrated